Rituximab in people living with HIV affected by immune-mediated renal diseases: a case-series. (December 2020) - Alfano, G; Giaroni, F; Fontana, F; Neri, L; Mosconi, G; Mussini, C; Guaraldi, G; Cappelli, G
Over the last two decades, rituximab (RTX) has played an important role in the treatment of some lymphoproliferative malignancies and immune-mediated diseases. RTX administration is generally safe and well-tolerated, but side effects including late-onset neutropenia, hypogammaglobulinemia, hepatitis B reactivation and rare cases of progressive multifocal leukoencephalopathy have been observed after its administration. Although there are no absolute contraindications regarding its use in people living with HIV (PLWH), the prescription of this drug has been principally limited in patients with oncohematological diseases. In this report, we described the outcome of four PLWH who underwent RTX therapy after the diagnosis of immune-mediated renal disease. The main RTX-associated adverse effects were leukopenia, late-onset neutropenia and decline of CD4+ and CD8+ T-cell counts. In addition, two of the four patients experienced pneumonia requiring hospitalization within six months from the last RTX infusion. We suggest that RTX should be used with caution in PLWH until further evidence emerges on its safety profile in this vulnerable population.